A global survey of national oral health policies and its coverage for young children - Gaffar, Balgis; Schroth, Robert J.; Foláyan, Moréniké Oluwátóyìn; Ramos-Gomez, Francisco; Virtanen, Jorma I. (Frontiers in Oral Health, 2024)
Background: There is no accessible information on countries with oral health policies. The purpose of this study was to identify World Dental Federation (FDI) member countries with oral health policies and their scope and extent of coverage of oral health care for young children.This international survey recruited chief dental officers, oral health advisors to national ministries of health, and other key informants of the 158 FDI member countries between December 2020 and December 2021. The survey tool was administered online to the study participants. Key questions explored the following outcome measures: countries with oral health policies; the thrusts of the oral health policies; policy thrusts targeting young children; and dental care plans as a component of a universal health care plan. Descriptive statistics were conducted to determine the number of countries with any of the study outcome measures and coverage per country.Results: Sixty (38%) of the 158 FDI member-countries responded to the survey. Forty-eight (55.2%) of the 60 countries had a national oral health policy document or position statement on oral health; 54 (62.1%) countries had plans on universal health care, and 42 (48.3%) included dental care within their universal health care plan. The most common policy thrusts addressing the oral health needs of children were the promotion of oral hygiene (71.7%), provision of fluoride products for children (53.3%), collaboration with primary care providers (35%), and prenatal oral health education (50%). There were differences in the scope of oral health care coverage and the coverage for young children between continents as well as between countries. Europe had many countries with children-friendly oral health policy coverage.Conclusions: About half of the surveyed countries had a national oral health policy. There were variations in the scope of oral health care coverage, particularly for young children, both between continents and among individual countries. These findings underscore the importance of understanding the landscape of oral health policies globally. Such insights can help inform targeted interventions to enhance oral health policies, thereby contributing to improved oral health outcomes on a global level.